PENGARUH PRAKTIK KERJA INDUSTRI DAN MOTIVASI KERJA TERHADAP KESIAPAN KERJA SISWA KELAS XII SMK - Putri, Zuyyina Hasdillah; H. Mashudi, H. Mashudi; Aminuyati, Aminuyati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractIndustrial Work Practices should provide sufficient provisions to prepare students to enter the business world and the industrial world. This effort was carried out in order to improve the quality of vocational high school graduates in creating education relevance to the demands of the workforce. This study uses a quantitative approach, the research method used is the relationship study method. The population in this study amounted to 98 people. The sample in this study amounted to 78 people. Collection techniques can be in the form of indirect communication techniques and documentary study techniques. Testing of the prerequisites used includes the Normality Test, Linearity Test, Multicollinearity test. Data Analysis The research used is Multiple Regression Analysis. Based on the results of the study, it can be concluded that industrial work practices have an effect on the work readiness of students of the SMTI class XII Pontianak, work motivation of students can influence the work readiness of students of class XII SMTI Pontianak. industrial work practices and work motivation together (simultaneous) affect the work readiness of students of class XII of SMTI Pontianak. Keywords : Industrial Work Practices, Pontianak SMTI Vocational School, Work Motivation, Work Readiness.